The Specialized Early Care for Alzheimer's method of caring for people with dementia: an investigation of what works and how. Issue 3 (12th December 2019) - McCrae, Niall; Penhallow, Jessica; Rees, Olivia; Norman, Ian
Abstract : Background and rationale: SPECAL is a model of care for people with dementia based on a novel conceptualisation of memory and how this changes in dementia. Carers adapt their communication style to prevent distress and promote well‐being for the person with dementia. However, there is limited scientific evidence on the effectiveness of SPECAL. Aim: This study explored mechanisms of SPECAL through a qualitative enquiry with family carers. Method: Semi‐structured interviews were conducted with family carers who had been coached in SPECAL and applied its principles and practices. Thematic analysis was applied. Findings: All participants had found SPECAL helpful in caring for a person with dementia. The core themes of this positive experience were empathy, harmony and resilience. Synthesis of these themes contributes to a proposed model of the mechanisms of SPECAL. Conclusion: In applying SPECAL, carers gained an empathetic insight to the feelings of the person with dementia. This empathy leads to a more harmonious environment, which enhances the carer's resilience.